2000
DOI: 10.1103/physrevb.61.r13333
|View full text |Cite
|
Sign up to set email alerts
|

Coherence effects in light scattering of two-dimensional photonic disordered systems: Elastic scattering of cavity polaritons

Abstract: Resonant scattering by cavity polaritons in a semiconductor microcavity is investigated. The bidimensional photonic behavior is well shown by the angular spread of the Rayleigh scattered light on the elastic cone. Moreover, the strong coupling between the excitonic oscillator and the cavity mode enables the simultaneous observation of both ͑i͒ universal properties of disordered systems such as coherent backscattering over a large angular width, and ͑ii͒ scattering anisotropy due to the microscopic nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 23 publications
3
56
1
Order By: Relevance
“…In our experiment we use a high finesse GaAs microcavity (F = 3000) with a polariton lifetime τ = 15 ps and a Rabi splitting of 5.1 meV [40][41][42] (see Appendix A: Sample description). The microcavity is excited with a continuous-wave single-mode Ti:Sa laser quasi resonant with the lower polariton branch at 837 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In our experiment we use a high finesse GaAs microcavity (F = 3000) with a polariton lifetime τ = 15 ps and a Rabi splitting of 5.1 meV [40][41][42] (see Appendix A: Sample description). The microcavity is excited with a continuous-wave single-mode Ti:Sa laser quasi resonant with the lower polariton branch at 837 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Organics offer the advantage of a broad spectral range beyond that covered by GaN and ZnO and can be easily fabricated without the need for epitaxial growth. As-grown films, however, tend to be highly disordered and to overcome possible localization effects [12][13][14][15][16][17][18][19][20][21][22][23][24], the first demonstration of organic polariton condensation used a single-crystalline organic semiconductor as the active material [1]. Two recent demonstrations, however, have shown that the same phenomenology can be extended to amorphous systems: one consisting of a spin-coated polymer [3] and the other of a thermally evaporated oligomer [2].…”
mentioning
confidence: 99%
“…Thus, when an initial polariton state with a given in-plane wavevector, k = (k x , k y ), and a given polarization state, transverse magnetic or transverse electric, is created, it is efficiently scattered towards states with in-plane wavevectors different from the initial one and with the same polarization state. As the modulus of k is conserved, this scattering gives rise to the Rayleigh scattering ring in the far-field emission 26,27 . Then the anisotropy in the orientation of the effective magnetic field creates an anisotropy in the polarization: in two opposite quadrants of the elastic circle, σ + polarization appears, whereas in the two others, σ − polarization appears (see Fig.…”
mentioning
confidence: 99%